Injury to endothelial cells by phagocytosing polymorphonuclear leukocytes and modulatory role of lipoxygenase products. - Vandenbroucke-Grauls, C M (1987)
Phagocytosis of microorganisms by polymorphonuclear leukocytes (PMN) is accompanied by inadvertent extracellular release of microbicidal products; this could result in tissue damage. We investigated whether PMN damages endothelial cells when phagocytosis of Staphylococcus aureus occurs on the endothelial surface and how this damage might be modulated. Damage was assayed by the measurement of cell detachment or cell lysis of cultured endothelial cells that were radiolabeled with 51Cr. Uptake of bacteria was accompanied by nonlytic detachment of endothelial cells from the monolayer. This effect was inhibited by alpha-1-antitrypsin but remained unaffected by scavengers of toxic oxygen species. During phagocytosis, PMN adhered to the endothelial cells. Adherence could be prevented by inhibition of the lipoxygenase pathway of arachidonic acid metabolism of the PMN with nordihydroguaiaretic acid. This inhibition also resulted in a marked decrease of the detaching activity of the PMN. The addition of exogenous leukotriene B4 during phagocytosis greatly enhanced the damage to the endothelial monolayer. These results indicate that phagocytosis of staphylococci by PMN is accompanied by injury to endothelial cell monolayers due to released lysosomal proteases and that products of the lipoxygenase pathway of PMN play a modulatory role in this injury.